2005
DOI: 10.1093/ndt/gfh928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral vitamin C supplementation on oxidative stress and inflammation status in haemodialysis patients

Abstract: Short-term oral vitamin C supplementation did not modify well-defined oxidative/antioxidative stress and inflammation markers in HD patients. Whether a higher oral dose or the intravenous route can modify these markers remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 24 publications
10
70
1
1
Order By: Relevance
“…iron treatment (48). In contrast to our results with juice, antioxidant supplements such as the N-3 fatty acid docosahexaenoic acid or vitamins C and E were not found to decrease the protein carbonyl content in hemodialysis patients (10,11). Further juice intervention studies in hemodialysis patients utilizing the protein carbonyl content as biomarker have not been described yet.…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiocontrasting
confidence: 99%
See 1 more Smart Citation
“…iron treatment (48). In contrast to our results with juice, antioxidant supplements such as the N-3 fatty acid docosahexaenoic acid or vitamins C and E were not found to decrease the protein carbonyl content in hemodialysis patients (10,11). Further juice intervention studies in hemodialysis patients utilizing the protein carbonyl content as biomarker have not been described yet.…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiocontrasting
confidence: 99%
“…Blood sampling was done after each experimental week (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Samples were drawn immediately before the beginning of the dialysis session, 1 to 2 h after juice ingestion.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance, C3f fragments have been found in the sera of patients with myocardial infarction but not in healthy controls (186). Although several polypeptides were affected/normalized by short-term oral vitamin C supplementation, the authors were not able to find any significant difference between classic oxidative/antioxidative stress and inflammation markers under vitamin C supplementation (187). Taken together, proteome analysis of plasma, urine, and dialysis fluid by proteomic analysis represents a sensitive and valuable new tool to pinpoint new molecular changes associated with uremia.…”
Section: Proteomics-a New Era Of Research In Ckdmentioning
confidence: 82%
“…200 mg/d [18], 800 IU/d [19] and 1,200 IU/d [20]). With regard to vitamin C, three studies found statistically significant treatment effects [21][22][23], and two found no treatment effect [28,29]. Firm conclusions are difficult to draw from these studies due to the wide variation in doses used and the differing lengths of each intervention.…”
Section: Discussionmentioning
confidence: 99%
“…As for ADMA, therapies that lower CRP as a marker of inflammation may therefore be expected to reduce CVD risk. A number of studies have suggested that antioxidant supplementation may lower CRP [18][19][20][21][22][23], but this is not always consistent [24][25][26][27][28][29][30]. Similarly, increasing levels of tHcy in cell cultures seems to promote IL-6 production by monocytes [31] and endothelial cells [32] and, therefore, B vitamins may also reduce CRP as a result of their tHcy-lowering potential.…”
Section: Introductionmentioning
confidence: 99%